Records Management Practices in Uganda's Public Pension Office - Kaddu, Sarah; Ssekitto, Francis; Kyarimpa, Moreen M. (University of Dar es Salaam Library Journal, 2022)
The purpose of this study was to assess the records management practices in Uganda's public pension office. The study's objectives were: to find out the categories of records managed in Uganda's public pension office; to examine the records management practices in Uganda's public pension office; to find out the challenges faced in the management of records in Uganda's public pension office, and to propose strategies to improve the management of records in Uganda's public pension office. The study adopted a mixed methods research design. It was conducted at the Ministry of Public Service, specifically in the Compensation Department and Department of Records and Information Management. The study population was composed of thirty (30) staff working in the two departments, who were all adopted as the sample size, given the small population. Data were collected through semi-structured interviews, self-administered questionnaires and a document review. The findings revealed that personnel records were mostly kept and that the records management practices followed were guided by the Basic Registry Procedures Manual, a manual specifically developed for registries at the Ministry of Public Service. Despite having a records manual in place, some staff had poor attitudes towards records management due to poor remuneration while others had no/limited training in records management. Other challenges faced included inadequate equipment, non-streamlined records management practices and a lack of a Centre for benchmarking its practices as stipulated by the National Records and Information Management Policy framework. It is expected that the findings revealed by this study will inform policymakers, the government of Uganda and the Ministry of Public Service on the key issues to solve in a bid to strengthen records management in the public pension office to enhance the process of pension processing which is usually delayed by the lack of records.